The Classification of Complex Sentences in French - Juraeva Malokhat Mukhammadovna; Sabirova Sabina Olimovna (Indonesian Journal of Innovation Studies, 2022)
The article analyzes various classification approaches to studying a complex sentence(CSP) of the French language: functional, according to which the subordinate clauses are functionallylikened to one or another member of a simple sentence; morphological, when the adnexaa part is equated to a certain part of speech; formal, based on grammatical means of communication,as a result of which the analysis of subordinate parts is reduced to the characteristics of unions andallied words; semantic, taking into account the structural and semantic features of the NGN.